2014
DOI: 10.1177/0950017014529008
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment and attitudes to work: asking the ‘right’ question

Abstract: Attitudes research has repeatedly demonstrated that the vast majority of unemployed people want a job, and that their work commitment is generally at least as strong as employed people's. But until now it has not asked if they are more likely than employed people to prefer unemployment to an unattractive job. While this oversight reflects a noted widespread reluctance to respond directly to right-wing authors' assertions, this article argues that it is partly attributable to existing studies using survey quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 22 publications
0
23
0
2
Order By: Relevance
“…The approach highlights the main focus of UK employment policy, which can be summarised in Bonvin and Farvaque's (2005: 277) Similarly, the importance attached to choice is founded on economic goals (Lewis and Giullari, 2005). The underlying, neo-liberal assumption is that unemployed individuals should, but do not, prefer any job to unemployment (Dunn et al, 2014). The level of required compliance that this approach entails was visible in court cases against the DWP (e.g.…”
Section: A Changing Policy Framework For Choicementioning
confidence: 99%
See 1 more Smart Citation
“…The approach highlights the main focus of UK employment policy, which can be summarised in Bonvin and Farvaque's (2005: 277) Similarly, the importance attached to choice is founded on economic goals (Lewis and Giullari, 2005). The underlying, neo-liberal assumption is that unemployed individuals should, but do not, prefer any job to unemployment (Dunn et al, 2014). The level of required compliance that this approach entails was visible in court cases against the DWP (e.g.…”
Section: A Changing Policy Framework For Choicementioning
confidence: 99%
“…On the one hand, and as the above quote indicates, without protective resistance it may be easier to 'get things done' and engage with the support and learning opportunities on offer. On the other hand, such change on the part of service users is equivalent to complying with attempts to change attitudes and behaviour by JC+ and the Work Programme (Dunn et al, 2014, DWP, 2014b.…”
Section: Overcoming Resistance and Approaching Choicementioning
confidence: 99%
“…This finding is backed up by new research which found that, on average, the workmotivation of unemployed people is significantly weaker than that of employed individuals (Dunn, Grasso & Saunders, 2014) Finally, Dunn and colleagues showed that when other variables were controlled for, unemployed people were still significantly more likely than employed people to prefer unemployment.…”
Section: Personality Of Welfare Claimantsmentioning
confidence: 74%
“…However, it should be noted that the causal mechanism could also be operating in the other direction, with protest having "biographical effects" on activists leading to nontraditional choices and irregular work histories (McAdam, 1999;Giugni & Grasso, 2016). Research has shown that some unemployed people are more resource-rich, preferring unemployment in the face of poor job alternatives (Dunn, Grasso, & Saunders, 2014). This in turn might attenuate the wider negative effects of losing a job and having a restricted network as a result of being out work (Jahoda, Lazarsfeld, & Zeisel, 1933).…”
Section: The Determinants Of Protest Participationmentioning
confidence: 99%